Articles of agreement made this 25th day of June, 1873, between the Anglo-American Telegraph Company Limited . of the first part, the Société du Câble transatlantique français . of the second part . Articles of agreement made this 26th day of June, 1873, between the New York, Newfoundland and London Telegraph Company . of the first part, The Anglo-American Telegraph Company Limited . of the second part, and The Newfoundland Land Company Limited . of the third part [electronic resource]. - Anglo-American Telegraph Company.; Société du Câble transatlantique français.; Newfoundland Land Company.; New York, Newfoundland & London Telegraph Company. ([S.l. : s.n., 1873)
Electronic reproduction. Mode of access: Internet. 44